Establishing an Intravesical Doublet Chemotherapy Clinic for Nonmuscle-Invasive Bladder Cancer Patients - Abou Chakra, Mohamad; Shore, Neal D; Brown, Erica S; Du, Guixin J; O'Donnell, Michael A (Urology practice, 2024)
Intravesical sequential doublet chemotherapy (SDC) is being used increasingly as a rescue treatment for nonmuscle-invasive bladder cancer failing bacillus Calmette-Guérin (BCG), as single-agent chemotherapies are less effective, especially for carcinoma in situ. Considering the current BCG shortage, intravesical SDC also provides an efficacious alternative to BCG. Our aim is to detail the implementation to assist with establishing an efficient and practical intravesical SDC clinic for urologic practice. We searched PubMed for published studies with the Medical Subject Heading of "intravesical chemotherapy" and "non-muscle invasive bladder cancer." The search was limited to English-language journals and full papers only. The initial search resulted in 260 articles, of which 20 relevant studies were selected. Five important processes were identified in the successful and efficient administration of intravesical SDC: (1) patient preparation, (2) medication procurement, (3) medication administration, (4) medication immediate aftermath, and (5) patient instruction and education. Safety precautions should be taken when handling each chemotherapy drug. A clinical pharmacist may be required for drug preparation. An important step in providing intravesical SDC is to use a closed system for the instillation of the chemo-solution. A special protocol should be adopted for every drug with its proper dwell time. The induction course consists of weekly instillation for 6 weeks. If an initial response is noted, maintenance therapy is recommended, typically monthly for 24 months. Successful intravesical SDC clinics necessitate appropriate patient selection, standardized workflow procedures, patient education, and good communication between the urologist, clinical pharmacists, and oncology nurses.